Communities in play : young preschool children's perspectives on relationships, values and roles - Hrönn Pálmadóttir 1954- (2015)
The overall aim of the thesis is to gain knowledge of young children’s perspectives on their communities in play in preschool. To accomplish this, four studies were conducted, each of them focusing on children’s perspectives on issues of importance for the creation of play communities with peers as well as their encounters with the educators and the researcher. The research was conducted with children aged one to three years, in two units in one preschool in Iceland. The first study focused on how the children communicated and expressed their desire to play with their peers. The second study centred upon children’s communication and expression of lived values, as well as their experiences according to their own and others’ behaviours, actions and meanings. The third study explored the meaning that children put into involving the educators into their play. The fourth study dealt with methodological challenges during the research process. The study is placed within the discourse of childhood studies and early childhood education and care (ECEC), where children are considered as active and competent with the ability to express their views and meanings (Clark & Moss, 2005; United Nations Convention on Children’s Rights, 1989). The research is inspired by phenomenological theories with the notion that children communicate and express their meanings with bodily expressions, and through their interactions, they learn about themselves and others (Merleau-Ponty, 1945, 1962), and play is considered a complex phenomenon that has its origins in the movements of the body (Bujtendijk, 1933; see Åm, 1989; Hangaard Rasmussen, 1996). The phenomenological approach is grounded within the paradigm of qualitative research. Data were constructed with observations by video recordings and field notes written during the research process. The fieldwork stretched over five month’s period in the year 2009. Children’s play sessions in the morning were chosen for data construction. Hermeneutics was used as the main approach to ...